Functionalized cell nucleus-penetrating peptide combined with doxorubicin for synergistic treatment of glioma. (15th September 2016) - Zhang, Li; Zhang, Yanyu; Tai, Lingyu; Jiang, Kuan; Xie, Cao; Li, Zhuoquan; Lin, Yao-Zhong; Wei, Gang; Lu, Weiyue; Pan, Weisan
Graphical abstract: Abstract: Clinical application of cell-penetrating peptides (CPPs) in cancer therapy is greatly restricted due to lack of tissue selectivity and tumor-targeting ability. CB5005, a rationally designed CPP that targets and inhibits intracellular NF-κB activation, is constituted by a unique membrane-permeable sequence (CB5005M) cascading to a NF-κB nuclear localization sequence (CB5005N). In vitro cellular evaluation confirmed that CB5005 was effectively taken up by brain capillary endothelial cell bEnd.3 and glioma cells U87. The intracellular localization analysis further demonstrated that CB5005 could not only penetrate into the cells but also enter into their nuclei. More interestingly, CB5005 permeated deeply into the tumor spheroids of U87 cell. In vivo imaging illustrated that the fluorescence-labeled CB5005 distributed itself into the brain and accumulated at the tumor site after intravenous injection. Given the important role of over expressed NF-κB in tumor growth and development, we further investigated CB5005 for its potential in treatment of glioma. When combined administration in vitro with doxorubicin (DOX), CB5005 exhibited a synergistic effect in killing U87 cells. In a nude mice xenograft model, CB5005 inhibited the growth of tumor when applied alone, and displayed a synergistic anti-tumor effect with DOX. In conclusion, CB5005 functioned simultaneously as a cell penetrating peptide and a tumor growth inhibitor, therefore can work as a potential synergist for chemotherapy of human tumor. Statement of Significance: Clinical application of cell-penetrating peptides in cancer therapy is restricted due to lack of tissue selectivity and tumor-targeting ability. In this manuscript, we reported a rationally designed peptide, named CB5005, which had an attractive capability of translocation into the cell nucleus and blocking nuclear translocation of endogenous NF-κB protein. CB5005 had unique affinity with brain and glioma, and could rapidly accumulate in these tissues after intravenous injection. Furthermore, CB5005 showed a synergistic effect on inhibiting gliomas when administrated with doxorubicin. This is the first literature report on this multi-functionalized peptide, which can work as a potential synergist for chemotherapy of tumor. This work should be of general interest to scientists in the fields of biomaterials, biology, pharmacy, and oncology.